Sarcoid dactylitis. Issue 6 (December 1983) - Pitt, P; Hamilton, E B; Innes, E H; Morley, K D; Monk, B E; Hughes, G R
Abstract : Dactylitis is a rare rheumatological complication of sarcoidosis. It may be accompanied by underlying bone changes, and management is often difficult. We report these 4 cases of dactylitis in which there have been significant bone changes and associated management problems. One case is further complicated by biopsy-proved sarcoid synovitis, uncommon in a British resident, and 2 cases show destructive bone changes, which have rarely been reported in sarcoidosis.